Socio-economic impact of museums - Murzyn-Kupisz, Monika (Journal of Public Governance, 2014)
Museums have a great, though still not fully acknowledged nor always used, potential to create diverse socioeconomic benefi ts at different spatial scales. The aim of the paper is to discuss important social and economic implications of museum activities which make it worthwhile to look at them not only as cost-generating enterprises and a ballast to public budget, or as institutions with an economic impact limited to supporting the tourism sector through providing the core of a tourism product. Departing from the consideration of museums as specific non-profit institutions producing a complex offer, the author points to a broad variety of museum stakeholders and defines various spheres of potential impact of museums.